Structural damage identification based on modal frequency strain energy assurance criterion and flexibility using enhanced Moth-Flame optimization. (December 2020) - Huang, Minshui; Li, Xifan; Lei, Yongzhi; Gu, Jianfeng
Abstract: The development of structural damage identification based on dynamic characteristics has been suffering from certain issues, such as low computational efficiency and lack of high-sensitivity damage indicators. In addition, the application of damage-sensitive objective function and efficient optimization technique control the success of damage identification as two key factors. To this regard, a damage identification framework based on modal frequency strain energy assurance criterion (MFSEAC), modal flexibility and enhanced moth-flame optimization is presented in this paper. To evaluate the performance of the proposed method, three benchmark functions are firstly used to validate the optimization performance of enhanced moth-flame optimization. The results indicate that enhanced moth-flame optimization can achieve better optimization results compared to moth-flame optimization, particle swarm optimization and cuckoo search. Three numerical examples, a 3-span concrete continuous beam considering gradient temperature variations, a 40-story shear frame under random noise and a 31-bar truss structure under the double influences of random noise and temperatures, are then practiced as comparisons by frequency change ratio (FCR) and modal assurance criterion (MAC), modal strain energy (MSE) and modal flexibility, in order to evaluate the damage identification accurateness of the proposed objective function. Finally, two laboratory examples, a simply supported steel beam and a 3-story shear steel frame, are applied to further verify the proposed method. According to the damage identification results, the proposed method features good environmental noise robustness, which boosts the efficiency of symmetric location damage identification.